The emotional impact of research: A reflexive account of a counsellor-turned-PhD researcher’s experience of vicarious trauma - Smith, Ruth (European Journal for Qualitative Research in Psychotherapy, 2021)
This article presents a personal and reflexive account of my experience as a counsellor-turned-researcher who experienced vicarious trauma as a counsellor and the impact this had while conducting counselling-related PhD research. I explore what is meant by “vicarious trauma” and the “emotional impact of research”, as well as presenting my own account to illustrate the impact of vicarious trauma on the qualitative research process. It is hoped that by sharing this account, other researchers, who may be negatively impacted by their research, will feel less isolated. Further, the use of post-critical ethnography as my PhD research methodology demands researcher reflexivity and critique of their positionality. This article is a way of achieving this. The article also contributes to the call for researcher self-care to be an institutionally recognised requirement of research approval as researcher wellbeing is often not prioritised in the way it is for research participants.